Palestine in the new world - Gottschalk, Max; American Jewish Committee; Hevesi, Eugene; Himmelfarb, Milton (New York : Research Institute on Peace and Post-War Problems of the American Jewish Committee, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joodse immigratie; zionisme; joodse staat; Palestijnse kwestie; Palestina